2021
DOI: 10.1080/23311975.2021.1875535
|View full text |Cite
|
Sign up to set email alerts
|

The role of human resource managers in the promotion of hotel sector as a brand in Jordanian hotel industry - a cross-sectional study

Abstract: This study assesses the impact of human resource managers on the effectiveness of hotel branding with reference to Jordanian hotel industry. The study followed a cross-sectional design in which data was collected through a questionnaire-based survey. Subsequently, the collected data were analysed using descriptive and multiple regression analysis. Findings of the study revealed that job satisfaction of the employee, employee effectiveness, employee selection, and employee retention strongly and significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Previous research has not shown precise results concerning consistent HRM and TQM categories in improving employee satisfaction, loyalty and performance (Al-Dhaafri and Alosani, 2020;Khdour, 2021;Richards, 2020). Nevertheless, the activities of employers have a considerable influence on employee views and expectations and firms' sustainability.…”
Section: Employee Branding Tqhrm and Employabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has not shown precise results concerning consistent HRM and TQM categories in improving employee satisfaction, loyalty and performance (Al-Dhaafri and Alosani, 2020;Khdour, 2021;Richards, 2020). Nevertheless, the activities of employers have a considerable influence on employee views and expectations and firms' sustainability.…”
Section: Employee Branding Tqhrm and Employabilitymentioning
confidence: 98%
“…The combined dimension of human resource management (HRM) and total quality management (TQM) is essential for developing sustainable organizations and obtaining a competitive advantage in attracting talent onboard. According to Khdour (2021), TQM directly and significantly affects HRM and its practices, leading to organizational performance. However, TQHRM practices alone may not be sufficient during uncertainties, and therefore, it is important to align with unique and sustainable organizational practices required to facilitate strong quality management (QM) and control processes at the workplace.…”
Section: Employee Branding Tqhrm and Employabilitymentioning
confidence: 99%
“…In some research on talent management practices, the focus is on the various talents of organizational employees that can help companies achieve success. That's because talented individuals are likely to do their job well and show outstanding performance in certain environments (Tarigan et al, 2018) Reviewing any organization's success depends on its employees' effective performance through effective human resource management practices (Khdour, 2021).…”
Section: Firm Perfomancementioning
confidence: 99%
“…On the other hand, lower employee competence leads to decreased organizational performance. Organizations must have capable employees to manage operations efficiently to ensure effective management, leading to improved employee performance (Khdour, 2021;Spector, 1986). Commission cannot be isolated from the processes and outcomes involved, as performance refers to the quality and quantity of work employees produce in fulfilling their assigned duties and responsibilities (Mohammad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%